1999
DOI: 10.1016/s0092-8674(00)81513-5
|View full text |Cite
|
Sign up to set email alerts
|

Electron Crystal Structure of an RNA Polymerase II Transcription Elongation Complex

Abstract: The structure of an actively transcribing complex, containing yeast RNA polymerase II with associated template DNA and product RNA, was determined by electron crystallography. Nucleic acid, in all likelihood the "transcription bubble" at the active center of the enzyme, occupies a previously noted 25 A channel in the protein structure. Details are indicative of a roughly 90 degrees bend of the DNA between upstream and downstream regions. The DNA apparently lies entirely on one face of the polymerase, rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 41 publications
3
26
0
1
Order By: Relevance
“…The central core domain of TFIIE34 was recently shown to also contain a winged helix motif (43). The structure of the RNAPII elongation complex has revealed an important DNA bend in the region of the TIS (47). Second, RNAPII was found to crosslink to the promoter DNA from nucleotides Ϫ39/Ϫ40 to ϩ13 in the absence of TFIIH (51) and from nucleotides Ϫ55 to ϩ32/ϩ34 in the presence of TFIIH (this report).…”
Section: Topological Organization Of a Tbp-tfiib-tfiif-rnapii-tfiie-tmentioning
confidence: 77%
See 1 more Smart Citation
“…The central core domain of TFIIE34 was recently shown to also contain a winged helix motif (43). The structure of the RNAPII elongation complex has revealed an important DNA bend in the region of the TIS (47). Second, RNAPII was found to crosslink to the promoter DNA from nucleotides Ϫ39/Ϫ40 to ϩ13 in the absence of TFIIH (51) and from nucleotides Ϫ55 to ϩ32/ϩ34 in the presence of TFIIH (this report).…”
Section: Topological Organization Of a Tbp-tfiib-tfiif-rnapii-tfiie-tmentioning
confidence: 77%
“…TBP binds to TFIIB and TFIIE; TFIIB binds to TFIIE and TFIIF; RNAPII binds to TBP, TFIIE, TFIIF, and TFIIH; TFIIF binds to TFIIE; and TFIIE binds to TFIIH. The structure of RNAPII has been modeled to account for both the dimension of the yeast enzyme and the presence of a 2.5-nm channel that can accommodate the promoter DNA and can exist in either an open or closed conformation (7,9,47,72). Finally, the structure of TFIIH is according to electron microscopy determination (55).…”
Section: Topological Organization Of a Tbp-tfiib-tfiif-rnapii-tfiie-tmentioning
confidence: 99%
“…DNase I footprinting analysis revealed that addition of a protein fraction containing TFIIE, TFIIF, and TFIIH to promoter-bound complexes that include RNA polymerase II, TBP, and TFIIB results in specific protection of promoter DNA between positions ϩ20 and ϩ30 (32). Results of two-dimensional electron crystallography performed on yeast RNA polymerase II transcription complexes suggest that TFIIE binds to a polymerase domain that contacts downstream DNA (33)(34)(35)(36); because TFIIE and TFIIH bind specifically to one another (37,38), these findings suggest that TFIIH might be similarly positioned. Results of two recent cross-linking studies are also consistent with the idea that TFIIH makes protein-DNA contacts downstream of the RNA polymerase II initiation complex during transcription initiation and, by extension, during promoter escape (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of RNase H prevents the formation of long DNA-RNA hybrids and allows pol II to establish a transcription bubble (34). The tailed-template approach was used to obtain the first crystal structures pol II elongation complexes (35,36). The proteins used in this study included four chaperones (ASF1, NAP1, FACT, and SPT6), two ATP-dependent remodeling machines (SWI/SNF and RSC), and pol II.…”
Section: Rsc-dependent Pol II Elongation Is Stimulated By Nucleosomementioning
confidence: 99%